Matemática e as fake news - Mendes, Daniel Machado (2021)
First of all, this work aims to present the concepts, characteristics and meanings of fake news, a term widely used in social media and practically spoken and discussed in all sectors of society. It will be dealt with the conception of post-truth today and its individual implications, in the life of the population and of credible institutions. Then, some fake news that appeal to Mathematics to consolidate and spread will be discussed, will be treated in a technical way, using Mathematics contents taught in basic education. Based on several authors, this information that went viral, - in the opinion of this researcher, together with the authors and research data from respected institutions - in fact, they are true or false, will stand out. Soon thereafter, tools will be proposed to combat these malicious information disclosure practices. It is believed that an education that proposes critical, reflective and democratic thinking can provide the whole society with instruments that face these practices. It is also believed, as it is the focus of this study, that mathematics is essential in this struggle, as it has elementary characteristics for the understanding of statistical data disclosed, in the understanding and articulation in financial/economic movements and in the analysis of primordial circumstances in the taking of decision in any life situation. It ends with methodologies that can assist in the teaching and learning of Mathematics, which take into account the community in which the students are inserted and their social characteristics, in order to have a teaching geared towards everyday life and its applications in the future life like person.